Nanomaterials: breaking the bottleneck of breast cancer drug resistance - Guan, Chao; Han, Yahao; Ling, Zhenzheng; Meng, Xiang; Zhang, Baolin; Dong, Wanwei; Zhang, Di; Chen, Keyan (Frontiers in Immunology, 2024)
Drug resistance poses a significant challenge in the treatment of breast cancer. In recent years, a variety of nanomaterials have been discovered and synthesized that can selectively target tumor cells and play a crucial role in the advancement of breast cancer therapies. As our understanding of tumor heterogeneity deepens, the emerging potential of nanomaterials in addressing drug resistance has garnered considerable attention. These materials not only selectively target tumor cells but also possess unique properties that make them promising options for cancer treatment, including low toxicity, excellent biocompatibility, ease of preparation, the ability to carry antitumor drugs, and customizable surface functions. In this review, we will comprehensively summarize two key developments in breast cancer treatment: the application of antitumor drugs and nanomaterials. We will explore the mechanisms by which nanomaterials improve drug resistance in breast cancer, targeted nanotherapy strategies to mitigate this resistance, and recent research advancements in anticancer nanomaterials. This overview aims to highlight the significant role of nanomaterials in breast cancer treatment and provide a theoretical framework for identifying optimal treatment strategies in the future.